(untitled) (Bangladesh Journal of Medical Science, 2012)
From December 2000 to November 2009, 10 cases of closed fracture which were usually needed definitive operative treatment were included in this study. All the patient were adult. Among them 8 patients were male and 2 were female. Patients were initially treated by Kabiraji method by indigenous physicians and ultimately referred to district hospital within 7 days to 6 weeks. All the fractures were treated by conservative method and the fractures were healed within 3 months. ROM were full. Among the fracture 3 were Galeazzi fracture dislocation, 5 were fracture radius and ulna and 2 were fracture shaft of femur. Average age of the patients were 28years. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9508 BJMS 2011; 10(4): 302-303